Empirical Research on Key Factors of Social Presence: Comparison of Three Universities - Ery Tri Djatmika; Muhammad Bukhori Dalimunthe; Punaji Setyosari; Heri Pratikto; Rosmala Dewi; Reza Aditia (Postgraduate, University of Mataram, 2023)
This study investigates how cognitive presence and affective connectedness impact social presence. We employed Partial Least Square (PLS-SEM) to analyze the data (N=679). Respondents were gathered from an online survey questionnaire by Indonesian and Malaysia undergraduate students in three universities: Universitas Negeri Medan (n=405), Universitas Negeri Malang (n=215), and Universiti Putra Malaysia (n=59). The result of this study indicates that in terms of the overall sample, cognitive presence and affective connectedness were found to have a positive and significant effect on social presence. If we peel the sample based on three universities, the result is consistent in Universitas Negeri Medan and Universiti Putra Malaysia samples. However, not the case in Universitas Negeri Malang. In this sample, affective connectedness was found to not significantly impact social presence. The findings are discussed in detail related to the key factors of social presence that have unique characteristics from the three campuses. This study suggests that in establishing students’ social presence, the teacher needs to utilize learning that intensifies cognitive presence and affective connectedness in order to foster the social presence.